2016
DOI: 10.1039/c5tb02041g
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor-targeting, enzyme-activated nanoparticles for simultaneous cancer diagnosis and photodynamic therapy

Abstract: On-site activated diiodostyryl bodipy conjugated HA nanoparticles with specific targets synthesized via self-assembly were used for the suppression of tumor growth and exact tumor diagnosis with reduced side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…[63] Dong and co-workers recently described a protein-activated theranostic agent. [64] This system is composed of nanoparticles Adv. Funct.…”
Section: Enzymes/proteins Overexpressed In Cancer Cells Activate Specmentioning
confidence: 99%
“…[63] Dong and co-workers recently described a protein-activated theranostic agent. [64] This system is composed of nanoparticles Adv. Funct.…”
Section: Enzymes/proteins Overexpressed In Cancer Cells Activate Specmentioning
confidence: 99%
“…An updated overview on the development of new photosensitizers for anticancer photodynamic therapy was reported by Zhang et al, [30]. More clinical studies of the efficacy of PDT and PTT using various nanoparticles have been reported [31][32][33][34][35][36][37][38][39].…”
Section: Discussion Of Combined Ptt and Pdtmentioning
confidence: 99%
“…In most cases, the core–shell structure of polymeric nanoparticles comprises a hydrophilic surface layer for stabilizing in blood circulation and a hydrophobic interior core for loading therapeutic agents including anticancer drugs or PSs . Encapsulating BODIPY PSs with a tumor‐targeting amphiphilic polymer to generate nano‐photosensitizers is a promising strategy to overcome the drawbacks of self‐assembly NPs and enhance photosensitizer concentration in the tumor …”
Section: Bodipy Nano‐photosensitizers For Pdtmentioning
confidence: 99%
“…Shi et al grafted diiodostyryl BODIPY to hyaluronic acid (HA), causing the spontaneous assembly of uniform NPs in water with a mean diameter of 50 nm ( Figure ) . These NPs exhibited specific tumor targeting due to the overexpression of the HA receptor, CD44, in tumor cells.…”
Section: Bodipy Nano‐photosensitizers For Pdtmentioning
confidence: 99%
See 1 more Smart Citation